Maribor med prevratom in senžermensko pogodbo - Friš, Darko (Prispevki za novejšo zgodovino, 2020)
Based on the preserved archival and news paper materials as well as the existing scientific literature, the authors of the following contribution present the key events in the city of Maribor, the centre of the Slovenian province of Styria, in the decisive period and the pivotal year of 1919. This year was tumultuous ever since its beginning, as eventhe January events went down in history as momentous. They involved the replacement of the last Maribor mayor from the Austrian period Johann Schmiderer with Government Commissioner Vilko Pfeifer and the mass demonstrations on 27 January, which have been preserved in the people's memory for more than acentury as "Bloody Sunday" (even though they took place on a Monday) and represented the culmination of the mounting national tensions between the Slovenian and the German population. In the year under consideration, the cityof Maribor underwent bureaucratic, economic, and political changes and faced national tensions, the struggle for the northern border, the "Maribor Treaty" in February, as well as the eagerly anticipated recovery after the end of the Great War.
Keywords: 1919; Bloady Monday; history; krvavi ponedeljek; Maribor; narodna trenja; national tensions; Pfeifer, Vinko; pivotal events; prelomni dogodki; Schmiderer, Johann; Slovenia; Slovenija; zgodovina